Cover Picture: Direct Energy Extraction from Brown Macroalgae‐Derived Alginate by Gold Nanoparticles on Functionalized Carbon Nanotubes (ChemCatChem 1/2014). Issue 1 (January 2014) - Hoa, Le Quynh; Yoshikawa, Hiroyuki; Saito, Masato; Ueda, Mitsuyoshi; Shibata, Toshiyuki; Tamiya, Eiichi
<x xml:space="preserve">Abstract</x> Brown and gold The cover picture illustrates the concept of using gold nanoparticle‐decorated carbon nanotubes to directly electrochemically oxidize alginate—the principle, difficult‐to‐degrade component of brown macroalgae (as shown in the background of the cover picture). In their Full Paper on p. 135 ff., L. Q. Hoa, E. Tamiya et al. present analyses that suggest a reaction pathway similar to the chemical oxidation process by strong oxidants that results in oxidized alginate usable for cell and tissue engineering. This straightforward approach, in contrast to currently employed alginate‐metabolizing microbial approaches, can enhance the energy extraction efficiency of the whole biomass‐to‐energy conversion process through a fuel cell system without requiring any external energy, while simultaneously producing high‐value chemicals, paving the way for the future production of energy and feedstock materials from inedible biomass.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>